The Interplay of Education and Age on Happiness: Bridging Analysis with Islamic Values - Rakhmawati, Rakhmawati (Universitas Muhammadiyah Yogyakarta, 2025)
Building upon the growing interest in the determinants of subjective well-being (SWB), this study analyzes the interaction between education and age on subjective well-being (SWB) in Indonesia. The novelty of this research lies in the finding that the relationship between age and SWB depends on education. This finding has yet to be widely discussed in the literature on the relationship between age and SWB, which mostly concludes that age and SWB exhibit a U-shaped pattern. Happiness, the dependent variables, is used as proxy for SWB. The data is the latest wave of the Indonesian Family Life Survey (IFLS), provided by RAND Corporation. Generalized ordinal logistic regression, or the partial proportional odds model, is employed as the estimation method, considering the ordinal nature of the dependent variables in this study and the violation of the proportional odds assumption. The findings indicate that increased level of education strenghten the positive the relationship between age and SWB, up to a certain point. However, the results suggest that for individuals with higher levels of education, the probability of feeling very unhappy may increase with age, particularly after age 70. Based on the findings, it is recommended that policies aim to provide educational opportunities for individuals, especially in their earlier years, to promote well-being and reduce the likelihood of negative outcomes such as feeling very unhappy in later life. From an Islamic perspective, the balance between worldly knowledge and spiritual well-being is emphasized. As individuals age, particularly those with higher education, managing expectations becomes crucial. Islam encourages individuals to be content (shukr) with their life circumstances and to find peace in their trust in Allah (tawakkal). This study found that religiosity and contentment significantly influence happiness. Therefore, policies should focus on educational opportunities and integrate support for spiritual well-being, helping individuals cultivate gratitude and inner peace as they age.